Pharmacy Students’ Proclivity Towards Entrepreneurship – A Sign of Future Innovation in Pharmaceutical Care Service Delivery. (2019)
Background:Entrepreneurial inclination is linked with improved pharmaceutical care service innovations and improvements. Objective: This study examined the propensity of pharmacy students towards entrepreneurship and factors influencing this. Material and Methods:Two hundred and eighty-one pharmacy students at the University of Ibadan participated in a two-year prospective study using a self–administered validated Pharmacy Students Entrepreneurial Orientation summated scale questionnaire with five subscales in seven-points Likert scale type graded responses. Mean and percentage mean scores were determined with a high mean score indicative of entrepreneurial tendency. Results:Percentage mean score for PSEO were 88.5% and 88.8% for the first and second year of the survey, respectively. Post-graduation business ownership intentions were high (83.0%) in both years. These intentions had significantly higher mean scores on PSEO scale (p<0.001), empathic super salesperson subscale (p=0.007), innovativeness subscale (p<0.001), and risk taking subscale (p=0.024), in the first year of survey. Pharmacy students who had taken business courses had higher PSEO mean scores than those who had not taken business courses (p=0.003). Male pharmacy students were more likely to take risks more than their female counterparts in the first year of the study (p=0.035). Conclusion:Pharmacy students maintained a high level of entrepreneurial tendency in both years of the study with most students aspiring to become business owners. Male pharmacy students were more inclined to take risk and hope to be innovative in pharmaceutical care services. To further strengthen entrepreneurial inclination, pharmacy schools curricula should include entrepreneurial courses.